The Exploration of Learner's Response to Illustrations in Short Stories Case study: Pupils of first year English Department -Laghouat - Bougrine, Bochra; Benredda, Djamal (University of Ammar Theledji -Laghouat, 2021)
With the development of technology , still the old method in teaching help learners to achieve their learning process , in addition to that , illustrations are the helping point to many of learners especially teenagers . The aim of this study was to determine the impact of illustrations in short stories on teenagers’ responses . This research study provides a framework about teaching and learning the four skills and how do learners response to illustrations in short stories Also it deals with the importance of illustrations and it can help teachers to make learners better learners .A questionnaire used to collect data which is a first year students of Amar Theleji university responses’ . The results of the questionnaire shows that the majority of learners prefer to read short stories with illustrations